Aprendizagens, práticas musicais e sociabilidade na Associação Os Gideões Internacionais no Brasil - Ribeiro, Ricardo Soares (2018)
This research focuses on the production of media in The Gideons International Association in Brazil. The activities related to the Association have been associated with musical practice, mainly non-written, and the events are inspired by the degrees generally promoted by the association where it is possible to contemplate the execution of chants founded, for the most part, that is, of European hymnology and North American The area of Education has a current perspective of a series of spaces and moments related to the teaching and learning of music, which has made possible reflections, interactions and discussions in the context of the construction of different pedagogical knowledges. In this sense, the objective is to investigate how music learning takes place in the association The Gideons International in Brazil. The objectives specified are: 1) to define international relations in Gideon; 2) investigate in a way the association The Gideons International experience the musical practice; 3) analyze a musical learning from collective singing; 4) understand how sociability relationships interfere in the musical learning process. This is a qualitative research, whose empirical field consists of participants from a unit of the Association, João Pessoa Norte. The techniques of data collection used were interviews, questionnaires and observations. The axes that guided the discussion were: the musical profile of the participants, the Association as a space for socialization, the members' musical baggage, the musical practices and the repertoire used. The study was relevant to the area of Music Education as teachers attentive to the recognition of the musical baggage of their students, friendship and camaraderie in the classroom, as well as appreciation of the student's speech. Another relevant aspect is the perception of the musical dialogue in a format of relaxation before an exacerbated rigor that can "plaster" the musical performance. It should also be highlighted that another relevant point for the area is in the sense of proposing a space that integrates students with different levels of learning.